The impact of welfare benefits on natives' and immigrants' attitudes towards immigration - Peter Huber; Doris A. Oberdabernig (WWWforEurope, 2015)
We investigate whether the dependence of immigrants on welfare benefits leads to opposition to further immigration by natives and immigrants in a pooled cross-section of 21 European countries for the 2004-2010 period. Explicitly controlling for the dependence of immigrants and natives on benefits we find that higher benefit take-up rates among immigrants than among natives lead to less favourable attitudes of natives towards immigration. Interestingly, we do not find similar stylised facts for immigrants' attitudes towards immigration.
Keywords: F22; J15; H53; I38; 330; Immigration; welfare state; migration attitudes